2022
DOI: 10.3390/e24111555
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of Hopfield-Type Neural Networks with Modulo Periodic Unpredictable Synaptic Connections, Rates and Inputs

Abstract: In this paper, we rigorously prove that unpredictable oscillations take place in the dynamics of Hopfield-type neural networks (HNNs) when synaptic connections, rates and external inputs are modulo periodic unpredictable. The synaptic connections, rates and inputs are synchronized to obtain the convergence of outputs on the compact subsets of the real axis. The existence, uniqueness, and exponential stability of such motions are discussed. The method of included intervals and the contraction mapping principle … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 33 publications
0
1
0
Order By: Relevance
“…It is well known that the human brain nervous system has abundant chaotic discharge behaviors [ 4 ], which are closely related to advanced intelligence. HNNs are considered to be the best example of studying the dynamics of the brain’s nervous system [ 5 , 6 ]. At the same time, many researchers have found that neural networks with chaotic behavior have a wide range of applications in many fields including associative memory, pattern recognition, and combinatorial optimization [ 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…It is well known that the human brain nervous system has abundant chaotic discharge behaviors [ 4 ], which are closely related to advanced intelligence. HNNs are considered to be the best example of studying the dynamics of the brain’s nervous system [ 5 , 6 ]. At the same time, many researchers have found that neural networks with chaotic behavior have a wide range of applications in many fields including associative memory, pattern recognition, and combinatorial optimization [ 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%